Toll-like Receptor 5 Activation by the CagY Repeat Domains of Helicobacter pylori - Tegtmeyer, Nicole; Neddermann, Matthias; Lind, Judith; Suneesh Kumar, Pachathundikandi; Sharafutdinov, Irshad; Gutiérrez-Escobar, Andrés Julián; Brönstrup, Mark; Tegge, Werner; Hong, Minsun; Rohde, Manfred; Delahay, Robin M.; Sticht, Heinrich; et al. (Cell Reports, 2020)
Helicobacter pylori (Hp) is an important human pathogen associated with gastric inflammation and neoplasia. It is commonly believed that this bacterium avoids major immune recognition by Toll-like receptors (TLRs) because of low intrinsic activity of its flagellin and lipopolysaccharides (LPS). In particular, TLR5 specifically detects flagellins in various bacterial pathogens, while Hp evolved mutations in flagellin to evade detection through TLR5. Cancerogenic Hp strains encode a type IV secretion system (T4SS). The T4SS core component and pilus-associated protein CagY, a large VirB10 ortholog, drives effector molecule translocation. Here, we identify CagY as a flagellin-independent TLR5 agonist. We detect five TLR5 interaction sites, promoting binding of CagY-positive Hp to TLR5-expressing cells, TLR5 stimulation, and intracellular signal transduction. Consequently, CagY constitutes a remarkable VirB10 member detected by TLR5, driving crucial innate immune responses by this human pathogen.
CRIS-Team Scopus Importer:2020-09-25
Keywords: CagY; flagellin; Helicobacter; innate and adaptive immunity; PAMP; PRR; signal transduction; T4SS; TLR5; type IV secretion